New mobility Scheme based on SDN in Wi-Fi network - et. al., Hind Sounni, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The massive use of wireless device and the increasing of traffic volume lead to find solutions to extend the coverage and increase wireless LANs' capacity. Given the distributed nature of 802.11-based WLANs, the existing solutions can become inefficient. Mobility is one of the main challenges when implementing a Wi-Fi network. Most mobile devices require a permanent connection to the desired services. An interruption of these services can occur during handover, i.e., when the access point is changed. This paper proposes a new mobility scheme based on an emerging technology called Software-Defined Networking (SDN). This technology allows centralized management, dynamic, automated configuration, and planning of the wireless network. A network simulation using Mininet Wi-Fi is done to analyze and compare the proposed mobility scheme's performance to the existing mobility protocol (PMIPv6). The results are very promising and prove the efficiency of our mobility system